2002
DOI: 10.1038/sj.hdy.6800008
|View full text |Cite
|
Sign up to set email alerts
|

Response of Sod-2 enzyme activity to selection for high voluntary wheel running

Abstract: The objective of this study was to examine the correlated response of anti-oxidant enzyme activity to selective breeding for increased voluntary wheel running in house mice. Activity of liver superoxide dismutase-2 (Sod-2), a free radical scavenger, was measured in four groups of mice. 'Active' individuals were housed in cages with attached wheels for 8 weeks beginning at weaning; 'sedentary' individuals were housed in cages with attached wheels that were prevented from rotating. Both of these treatments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Circadian variation in SOD enzyme activity is observed in primate erythrocytes [45]. Interestingly, genetic selection of mice for increased wheel running is associated with decreased MnSOD activity in liver tissue [46].…”
Section: Discussionmentioning
confidence: 99%
“…Circadian variation in SOD enzyme activity is observed in primate erythrocytes [45]. Interestingly, genetic selection of mice for increased wheel running is associated with decreased MnSOD activity in liver tissue [46].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, perhaps resistance‐conferring allele(s) have narrower effects than on the partitioning of a general resource pool. For example, a specific resource may have been diverted to resistance critical for reproduction but not for survival, or pleiotropic effects may have been exerted on structures, enzymes (e.g., Thomson et al 2002), or behaviors specifically related to oogenesis or oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…We would thus predict (H1) that selection mice have faster aging and shorter life spans than control mice, and that this effect would be accentuated in the active environment. Some weak support for this hypothesis from an earlier generation of this system of mice is presented by Thomson et al (2002), who found lower Sod-2 activity in 15-week-old selection females regardless of activity environment; in males, a G ϫ E interaction was identified, with selection males having lower Sod-2 activity in the sedentary environment but higher Sod-2 activity in the active environment. Although activity of antioxidant enzymes is not directly correlated with longevity, the results of Thomson et al (2002) suggest some potential evolutionary costs to selection for high wheel-running activity.…”
mentioning
confidence: 97%